Problematika Penurunan Operasional Koperasi Unit Desa (Kud) Super Ganesa di Mariyai Kabupaten Sorong - Fitrah Ariyani (Prodi Ekonomi Syariah IAIN Sorong, 2021)
Based on the results of this study it can be concluded that; 1) There was an operational decline experienced by the Super Ganesa Village Unit Cooperative (KUD) due to (Natural Resources, the Concept of Cooperatives that are not correct, Finances owned, Low Work Ethic of Cooperatives and Lack of Development in terms of Technology); 2) The strategies that have been developed to help improve the operations of the Super Ganesa Village Unit Cooperative (KUD), one of which is (Improving the Quality of Human Resources in Cooperatives, the Need for Firmness in the Cooperative Concept, Strengthening from the Financial Side, Required Overhaul of the SHU Distribution System, and Increased Utilization of Information Technology ).